Subjective Outcome Evaluation of the Project P.A.T.H.S. (Extension Phase) Based on the Perspective of Program Implementer - Daniel T. L. Shek; Lu Yu (The Scientific World Journal)
A total of 231 schools participated in the Project P.A.T.H.S. in 2009/2010 school year. After completion of the Tier 1 Program, subjective outcome evaluation data were collected from 3,259 program implementers. Based on the consolidated data with schools as units, results showed that participants had positive perceptions of the program, implementers, and benefits of the program. More than four-fifth of the implementers regarded the program as helpful to the program participants. Multiple regression analyses revealed that perceived qualities of the program and the program implementers predicted perceived effectiveness of the program. Similar to previous studies, compared to implementers’ perception about their performance, the perceived program content appeared to be a stronger predictor of program success. The present study provides additional support for the effectiveness of the Tier 1 Program of the Project P.A.T.H.S. in Hong Kong.